Variability in Bromus brevis “pampeana” (brome grass) (Semiárida, 2020)
The objective of this study was to evaluate the variability of B. brevis Nees. Nineteen accessions were collected at different locations of La Pampa and Buenos Aires provinces and characterized in 1992 on the basis of agronomic characters. Accessions were arranged in a randomized complete block design with 3 replications. Analysis of variance and FLSD tests were performed. High variabi-lity (p
Keywords: Bromus brevis; "pampeana" brome grass; agronomic characters variability